2014
DOI: 10.1136/bcr-2013-201038
|View full text |Cite
|
Sign up to set email alerts
|

Vocal cord paralysis associated with Ramsay Hunt syndrome: looking back 50 years

Abstract: Ramsay Hunt syndrome is defined by herpes zoster oticus and peripheral facial nerve palsy which is often associated with otalgia. The syndrome is, in rare cases, associated with other cranial nerve paralyses including the vagal nerve causing unilateral vocal cord paralysis. Vocal cord paralysis is more often seen as a symptom of various other diseases, that is, malignant tumours, neurodegenerative illness, cerebrovascular assaults, inflammatory processes or as a result of intubation or surgical procedures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Rasmussen reported that recovery of vocal cord paralysis was found in only 4 of 14 patients (28.6%), and facial paralysis was the same. 4) The above studies showed a difference in the recovery rate when facial paralysis occurred in the early stages. However, in our cases, the degree of facial paralysis was not severe as grade III or less, and recovery was observed after treatment.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Rasmussen reported that recovery of vocal cord paralysis was found in only 4 of 14 patients (28.6%), and facial paralysis was the same. 4) The above studies showed a difference in the recovery rate when facial paralysis occurred in the early stages. However, in our cases, the degree of facial paralysis was not severe as grade III or less, and recovery was observed after treatment.…”
Section: Discussionmentioning
confidence: 90%
“…In a paper analyzing RHS with polyneuritis combined with vocal cord palsy (CN X) reported in the literature for 50 years; of the 14 patients, the incidence was CN VII, VIII, IX, V, and XII. 4) There are few prospective controlled studies for RHS with multiple CN involvement in the medical literature. The actual management starts with a combination of an antiviral agent and steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) Paralyses secondary to viral infections exhibit a good prognosis with complete resolution in most patients, but early pharmacological therapy is important when the causal agent has been identified. (8)(9)(10) In paralyses with high suspicion of viral infection, imaging tests shall be conducted, in addition to a neurological examination, a lumbar puncture for CSF analysis and PCR to rule out encephalitis of the most common viruses, as well as serological testing for these most frequent viruses. (8,9) The mechanism whereby most of the viruses described may cause a BVFP is through reactivation that allows the virus to migrate through the nerves to the skin and other organs such as the CNS, causing cranial nerve paralysis, among other disorders.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10) In paralyses with high suspicion of viral infection, imaging tests shall be conducted, in addition to a neurological examination, a lumbar puncture for CSF analysis and PCR to rule out encephalitis of the most common viruses, as well as serological testing for these most frequent viruses. (8,9) The mechanism whereby most of the viruses described may cause a BVFP is through reactivation that allows the virus to migrate through the nerves to the skin and other organs such as the CNS, causing cranial nerve paralysis, among other disorders. (8-10) Some viruses can be neurotropic and capable of invading the different cells in the CNS, with the potential to develop various types of encephalitis and intracranial infections.…”
Section: Discussionmentioning
confidence: 99%